11-deoxycortisol positively correlates with T cell immune traits in physiological conditionsResearch in context - Chunying Peng; Xun Jiang; Martin Jaeger; Pepijn van Houten; Antonius E. van Herwaarden; Valerie A.C.M. Koeken; Simone J.C.F.M. Moorlag; Vera P. Mourits; Heidi Lemmers; Helga Dijkstra; Hans J.P.M. Koenen; Irma Joosten; et al. (EBioMedicine, 2024)
Summary: Background: Endogenous steroid hormones have significant effects on inflammatory and immune processes, but the immunological activities of steroidogenesis precursors remain largely unexplored. Methods: We conducted a systematic approach to examine the association between steroid hormones profile and immune traits in a cohort of 534 healthy volunteers. Serum concentrations of steroid hormones and their precursors (cortisol, progesterone, testosterone, androstenedione, 11-deoxycortisol and 17-OH progesterone) were determined by liquid chromatography-tandem mass spectrometry. Immune traits were evaluated by quantifying cellular composition of the circulating immune system and ex vivo cytokine responses elicited by major human pathogens and microbial ligands. An independent cohort of 321 individuals was used for validation, followed by in vitro validation experiments. Findings: We observed a positive association between 11-deoxycortisol and lymphoid cellular subsets numbers and function (especially IL-17 response). The association with lymphoid cellularity was validated in an independent validation cohort. In vitro experiments showed that, as compared to androstenedione and 17-OH progesterone, 11-deoxycortisol promoted T cell proliferation and Candida-induced Th17 polarization at physiologically relevant concentrations. Functionally, 11-deoxycortisol-treated T cells displayed a more activated phenotype (PD-L1high CD25high CD62Llow CD127low) in response to CD3/CD28 co-stimulation, and downregulated expression of T-bet nuclear transcription factor. Interpretation: Our findings suggest a positive association between 11-deoxycortisol and T-cell function under physiological conditions. Further investigation is needed to explore the potential mechanisms and clinical implications. Funding: Found in acknowledgements.